The history of illustration - Doyle, Susan, 1959-; Grove, Jaleen (S. Jaleen); Sherman, Whitney (New York : Fairchild Books, 2018)
"Written by an international team of illustration historians, practitioners, and educators, History of Illustration covers image-making and print history from around the world, spanning from the prehistoric to the contemporary. With hundreds of color image, this book to contextualize the many types of illustrations within social, cultural, and technical parameters, presenting information in a flowing chronology. This essential guide is the first comprehensive history of illustration as its own discipline. Readers will gain an ability to critically analyze images from technical, cultural, and ideological standpoints in order to arrive at an appreciation of art form of both past and present illustration"--
21. Counterculture since the 1960s: Underground Comix, Rock, and Protest Posters! -- 22. Contemporary Children's Book (1935-1995) -- 23. Contemporary Illustration: Shifting Markets in a Postmodern World -- 24. Continuing Strides in Medical and Scientific Illustration and Data-driven Visualization -- 25. Directions: Illustration as a "Future" Discipline Glossary -- Bibliography -- Index.
boek
Keywords: Graphic arts -- History; Art and society -- History; DESIGN / Graphic Arts / Illustration; ART / History / General